94 Catastrophic cheerleading injuries in the united states. (19th September 2017) - Yau, Rebecca; Dennis, Savannah; Boden, Barry; Cantu, Robert; Kucera, Kristen
Abstract : Background: Cheerleading is becoming increasingly popular in the United States (US). Although annual cheerleading participation statistics for both high school and college do not exist, National Federation of State High School Associations data show that the number of high schools with competitive spirit squads increased from 4644 in 2002 to 4916 in 2011, suggesting an increase in cheerleading participation. With this participation increase comes a potential increase in injuries. Purpose: This study describes the characteristics of catastrophic cheerleading injuries in the US from July 2002 through June 2012. Methods: Ten years of data were collected by the National Centre for Catastrophic Sports Injury Research. Information on catastrophic cheerleading injuries were compiled with the assistance of individuals involved in cheerleading (e.g., coaches, athletic trainers, athletes and families) and from public media reports (e.g., newspaper clippings, online news articles). A catastrophic injury was defined as a severe acute traumatic injury sustained during participation in cheerleading activities. Results: There were 52 catastrophic cheerleading injuries. Most cheerleaders injured were females (n=50) in high school (n=39) in the flyer position (n=37). Most injuries were sustained during practice activities (n=35) to the brain/head (n=26). Nearly half (46%, n=24) of all injuries involved permanent severe functional disability, and one injury resulted in death. High school cheerleaders sustained a greater proportion of injuries during practice than college cheerleaders (72% vs. 62%), and injuries occurring during practice were more likely to lead to permanent severe functional disability than those occurring during competition (56% vs. 31%). Conclusion: Catastrophic injuries may produce life-changing circumstances. Increased efforts to promote safety during cheerleading practices are warranted especially at the high school level. Contribution: Cheerleading is an activity that can lead to severe debilitating injuries; this descriptive epidemiology study provides the most recent snapshot of catastrophic cheerleading injuries in the US.